High broad-band photoresponsivity of mechanically formed InSe-graphene van der Waals heterostructures - Mudd, Garry W.; Svatek, Simon A.; Hague, Lee; Makarovsky, Oleg; Kudrynskyi, Zakhar R.; Mellor, Christopher J.; Beton, Peter H.; Eaves, Laurence; Novoselov, Kostya S.; Kovalyuk, Zakhar D.; Vdovin, Evgeny E.; Marsden, Alex J.; et al. (Wiley, 2015)
We exploit the broad-band transparency of graphene and the favorable band line up of graphene with van der Waals InSe crystals to create new functional heterostructures and high-performance photodetectors. The InSe-graphene heterostructure exhibits a high photoresponsivity, which exceeds that for other two-dimensional van der Waals crystals, and a spectral response that extends from the near-infrared to the visible spectrum. The highest photoresponsivity is achieved in device architectures where the InSe and graphene layers are vertically stacked, thus enabling effective extraction of photogenerated carriers from the InSe to the graphene electrodes.